Dipeptidyl peptidase-4 inhibitor treatment induces a greater increase in plasma levels of bioactive GIP than GLP-1 in non-diabetic subjects - Tsuyoshi Yanagimachi; Yukihiro Fujita; Yasutaka Takeda; Jun Honjo; Hidemitsu Sakagami; Hiroya Kitsunai; Yumi Takiyama; Atsuko Abiko; Yuichi Makino; Timothy J. Kieffer; Masakazu Haneda (Elsevier, 2017)
Objective: Glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) possess multiple bioactive isoforms that are rendered non-insulinotropic by the enzyme dipeptidyl peptidase-4 (DPP-4). Recently, some ELISA kits have been developed to specifically measure "active" GIP and GLP-1, but it is unclear if these kits can accurately quantify all bioactive forms. Therefore, it remains uncertain to what extent treatment with a DPP-4 inhibitor boosts levels of biologically active GIP and GLP-1. Thus, we evaluated our novel receptor-mediated incretin bioassays in comparison to commercially available ELISA kits using plasma samples from healthy subjects before and after DPP-4 inhibitor administration. Methods: We utilized cell lines stably co-transfected with human GIP or GLP-1 receptors and a cAMP-inducible luciferase expression construct for the bioassays and commercially available ELISA kits. Assays were tested with synthetic GIP and GLP-1 receptor agonists and plasma samples collected from subjects during a 75 g oral glucose tolerance test (OGTT) performed before or following 3-day administration of a DPP-4 inhibitor. Results: A GIP isoform GIP(1-30)NH2 increased luciferase activity similarly to GIP(1-42) in the GIP bioassay but was not detectable by either a total or active GIP ELISA kit. During an OGTT, total GIP levels measured by ELISA rapidly increased from 0 min to 15 min, subsequently reaching a peak of 59.2 ± 8.3 pmol/l at 120 min. In contrast, active GIP levels measured by the bioassay peaked at 15 min (43.4 ± 6.4 pmol/l) and then progressively diminished at all subsequent time points. Strikingly, at 15 min, active GIP levels as determined by the bioassay reached levels approximately 20-fold higher after the DPP-4 inhibitor treatment, while total and active GIP levels determined by ELISA were increased just 1.5 and 2.1-fold, respectively. In the absence of DPP-4 inhibition, total GLP-1 levels measured by ELISA gradually increased up to 90 min, reaching 23.5 ± 2.4 pmol/l, and active GLP-1 levels determined by the bioassay did not show any apparent peak. Following administration of a DPP-4 inhibitor there was an observable peak of active GLP-1 levels as determined by the bioassay at 15 min after oral glucose load, reaching 11.0 ± 0.62 pmol/l, 1.4-fold greater than levels obtained without DPP-4 inhibitor treatment. In contrast, total GLP-1 levels determined by ELISA were decreased after DPP-4 inhibitor treatment. Conclusion: Our results using bioassays indicate that there is a greater increase in plasma levels of bioactive GIP than GLP-1 in subjects treated with DPP-4 inhibitors, which may be unappreciated using conventional ELISAs. Keywords: Receptor-mediated incretin bioassays, Glucose-dependent insulinotropic polypeptide, Glucagon-like peptide-1, Dipeptidyl peptidase-4